PENERAPAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DENGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR IPS SISWA KELAS VIII H SMP NEGERI 1 MASARAN KABUPATEN SRAGEN TAHUN PELAJARAN 2014/2015 - Saptorini, Dyah; Joebagio, Hermanu; Agung S, Leo (HISTORIKA, 2015)
This reseasch is aimed : 1) to measure the teaching learning process applying STAD model with Audio Visual media in class VIII H SMP negeri 1 Masaran; 2) to describe the application of STAD model with Audio Visual media to improve the creativity of the student of class VIII H SMP negeri 1 Masaran; 3) to describe the application of STAD with Audio Visual media to improve learning achievement of class VIII H SMP negeri 1 Masaran.       This research is a classroom action research by using three ciclus each cycle consists of four stages: planning, action, observation, ang reflexion. For data collecting, it is done with test ang non-test. The forms of collecting data are written test, creativity questionnaire, and observation done with collaborator. With the adding values of STAD it is student are active to help and support the spirit to be successful and actively roles as peers’ tutor to enhance the groups success, it is proved to improve creativity and learning achievement.       This research shows that the application of STAD model with Audio Visual media can improve creativity and social learning achievement of students calss VIII H SMP negeri 1 Masaran in the year of 2014/ 2015. The result shows that students creativity scor in cicle I, it can be know that average is 42,3 or 53%, the second cycle is 47,3 or 59% and the third cycle is 55,2 or 69%. While the score of cognitive post-test learning outcomes average in first cycle is 74,26 with completeness achievement  55,88 %,  the second cycle is 78,12 with completeness achievement  76,47% and the third cycle is 81,78 with completeness achievement  85,29%. The implementation of STAD model through audio visual at social science learning can increase the creativity and achievement in the eighth graders of class H SMP Negeri 1 Masaran.